Trace element and U isotope analysis of uraninite and ore concentrate: Applications for nuclear forensic investigations. (September 2017) - Spano, Tyler L.; Simonetti, Antonio; Balboni, Enrica; Dorais, Corinne; Burns, Peter C.
Abstract: Uranium ore concentrate (UOC), is an important intermediate material in the nuclear fuel cycle. Trace element distributions in UOCs can be related to the geologic conditions in which the source uranium ore formed, and hence are characteristic for each deposit type. These chemical signatures can then potentially be used as an essential tool for nuclear forensic analysis of derivative radioactive materials. In this study, several samples of UOC and uraninite extracted from sandstone-hosted roll front deposits in the Powder River basin U province in Wyoming (USA) have been analyzed for their trace element abundances and U isotopic compositions. UOCs were analyzed both in solution mode-inductively coupled plasma mass spectrometry (SM-ICP-MS) subsequent bulk sample digestion, and at high-spatial resolution (10s of micron scale) using a laser ablation (LA)-ICP-MS technique. Comparison of trace elemental abundances obtained by SM- and LA-ICP-MS indicates corroborating results, with comparable chondrite-normalized rare earth element (REE) patterns; those obtained by LA-ICP-MS show a slightly larger variation in absolute elemental abundances compared with corresponding bulk sample digestions. U isotopic measurements for UOCs and uraninite were conducted by solution mode multi-collector (MC)-ICP-MS. 238 U/ 235 U, 235 U/ 234 U and 238 U/ 234 U ratios for uraninite and UOC overlap and confirm a lack of significant isotopic fractionation during the fabrication process. The results reported here assert the validity of analyzing UOC for source attribution purposes and simultaneously demonstrate that corroborating trace element signatures can be obtained with both LA and SM-ICP-MS analytical techniques for U-rich materials relevant to the nuclear fuel cycle. REE abundances and U isotopes did not fractionate during early ore processing of materials investigated in this study. Highlights: Corroborating trace element analyses are obtained regardless of sampling technique. No differentiation of trace element signatures occurs during U ore processing. U isotope ratios are established for corresponding U ore and ore concentrate. The origin of uranium ore concentrate is determined using forensic indicators.